Evaluation of porcine decomposition and total body score (TBS) in a central European temperate forest - Indra, Lara; Giles, Stephanie; Alfsdotter, Clara; Errickson, David; Lösch, Sandra (Wiley, 2024)
The total body score (TBS) is a visual scoring method to scale the succession of decomposition stages. It compares decomposition between cadavers, to connect it with external taphonomic factors and estimate the post-mortem interval. To study decomposition in various climatic environments, pigs are often used as human proxies. Currently, there is one TBS system by Keough et al. (J Forensic Sci. 2017;62:986) for surface-deposited domestic pigs, coming from South Africa. Our study aims to evaluate this method and analyze porcine decomposition in Central Europe to inform forensic research and casework. We conducted an experiment studying six 50 kg pig carcasses in a temperate Swiss forest. Three observers documented decomposition patterns and rated the decomposition stages from photographs based on the porcine TBS model by Keough et al. (J Forensic Sci. 2017;62:986). We documented discrepancies between the carcass decomposition of our specimens and those in the South African study, especially related to the high insect activity in our experiment. Furthermore, we noted factors complicating TBS scoring, including rainfall and scavengers. The agreement between TBS observers from photographs was in the highest agreement category apart from one “substantial agreement” category. Our study is the first in Europe to systematically test the Keough et al. (J Forensic Sci. 2017;62:986) method. The results evidence that regional adaptations are required to be applicable for other environments. We present a modified approach based on experimental observations in a Swiss temperate forest. The identification of regional decomposition patterns and drivers will inform future taphonomy research as well as forensic casework in comparable contexts in Central Europe.
Keywords: decomposition; forensic anthropology; forensic taphonomy; pig carcass; postmortem interval (PMI); total body score (TBS)